Fronteiras de imigração no caminho das águas do Prata: italianos em Mato Grosso 1856 a 1914 - Gomes, Cristiane Thais do Amaral Cerzósimo (2009)
In this work, dimensions and meanings of the Italian movement heading for the Province/State of Mato Grosso, through Prata basin, in the period from 1856 to 1914 are historically presented, considering different trajectories and experiences faced by those immigrants in the appropriation process and space re-appropriation in mato-grossense lands. The approach concerning the Italian presence in Mato Grosso, during the time of free navigation and the commercial connection with countries of Prata area, has as aim to investigate different ways of how those immigrant experiences were developed in cultural terms and how they were also consolidated to traditions, value systems, ideas and institutional ways of living, working and developing Mato Grosso. The present work was based on travelers reports and on province presidents reports and statements consular, ecclesiastic, memorials, journalistic, police and census and it made possible to accompany dimensions of ways of life of the mato-grossense population, and also the participation of Italians in the social constitution process of Mato Grosso, as well as factors of uprooting and the act of immigrating/re-immigrating of those historic agents. According to this perspective, from testimonies of successive generations of Italians in Mato Grosso, it was possible to know particularities of daily actions of those immigrants, living and sociability ways in many immigrant environments in Mato Grosso. Besides that it was possible to accompany different histories which took men, women and their children to abandon their own spaces, environments and origin regions heading for mato-grossense lands, through Prata basin